Exosome-derived microRNAs: emerging players in vitiligo - li, Wenquan; Pang, Yaobin; He, Qingying; Song, Zongzou; Xie, Xin; Zeng, Jinhao; Guo, Jing (Frontiers in Immunology, 2024)
Exosome-derived microRNAs (miRNAs) are biomacromolecules and nanoscale extracellular vesicles originating from intracellular compartments that are secreted by most cells into the extracellular space.This review examines the formation and function of exosomal miRNAs in biological information transfer, explores the pathogenesis of vitiligo, and highlights the relationship between exosomal miRNAs and vitiligo. The aim is to deepen the understanding of how exosomal miRNAs influence immune imbalance, oxidative stress damage, melanocyte-keratinocyte interactions, and melanogenesis disorders in the development of vitiligo. This enhanced understanding may contribute to the development of potential diagnostic and therapeutic options for vitiligo.